Comorbid social phobia does not predict the outcome in alcohol use disorder outpatient treatment. (1st December 2018) - Mellentin, Angelina Isabella; Mejldal, Anna; Nielsen, Bent; Søgaard Nielsen, Anette
Highlights: Among 3197 alcohol use disorder (AUD) outpatients, 15% had social phobia (SP). Patients with and without SP had a similar treatment courses and dropout rates. SP was not associated with inferior alcohol-related treatment outcomes. Abstract: Background: Social phobia (SP) is one of the most prevalent anxiety disorders among patients entering treatment for alcohol use disorders (AUD). However, few studies have examined the association between SP and alcohol-related treatment outcomes in naturalistic settings. Aims: The aims of this study were to estimate the prevalence of co-morbid SP and to investigate the impact of the co-morbidity on the treatment course, dropout rates and treatment outcomes in a large sample of AUD patients treated in an outpatient alcohol treatment clinic. Methods: The study was conducted as an observational cohort study. A consecutive sample of 3.197 treatment-seeking outpatients, with an AUD diagnosis according to the ICD-10 Diagnostic Criteria for Research, was assessed by means of the Addiction Severity Index at treatment start and at treatment conclusion. Results: Approximately 15% of the patients suffered from SP when entering treatment and patients with and without SP did not differ on the treatment course, compliance or dropout rates. SP did not predict any alcohol-related treatment outcomes either, where no association was found on change scores for abstinence, drinking days and days with excessive drinking relative to AUD patients without co-morbidity. Conclusion: AUD patients with and without co-morbid SP were equally likely to achieve benefits when treated similarly with evidence-based pharmacological and psychosocial approaches in a naturalistic setting.